In vitro inhibition of Mycobacterium tuberculosis β-carbonic anhydrase 3 with Mono- and dithiocarbamates and evaluation of their toxicity using zebrafish developing embryos. (1st January 2020) - Aspatwar, Ashok; Hammaren, Milka; Parikka, Mataleena; Parkkila, Seppo; Carta, Fabrizio; Bozdag, Murat; Vullo, Daniela; Supuran, Claudiu T.
Abstract: We investigated a panel of 14 compounds belonging to the monothiocarbamate (MTC ) and dithiocarbamate (DTC ) series against the β-carbonic anhydrase 3 ( β -CA3) of Mycobacterium tuberculosis (Mtb). We also evaluated all compounds for toxicity using 1–5-day post fertilisation zebrafish embryos. 11 out of the 14 investigated derivatives showed effective nanomolar or submicromolar in vitro inhibition against the β -CA3 (KI s 2.4–812.0 nM), and among them four DTCs of the series (8–10 and 12 ) showed very significant inhibition potencies with KI s between 2.4 and 43 nM. Out of 14 compounds screened for toxicity and safety 9 compounds showed no adverse phenotypic effects on the developing zebrafish larvae at five days of exposure. The results of in vitro inhibition and the toxicological evaluation of our study suggest that 5 compounds are suitable for further in vivo preclinical characterisation in zebrafish model.